Implementation of Role Play to Stimulate the Expressive Language Skills of 5-6 Year Old Children at Ngariboyo 2 Kindergarten, Magetan Regency - Rury Gianto Pribadi; Ida Yeni Rahmawati; Nurtina Irsad Rusdiani (LITERACY : International Scientific Journals of Social, Education, Humanities, 2025)
This study aims to describe the effectiveness of role-playing as a method to stimulate expressive language skills in children aged 5–6 years in Ngariboyo 2 Kindergarten, Magetan Regency. The research method applied was qualitative descriptive with a total of 16 research subjects in group B, consisting of 9 boys and 7 girls. Information was obtained through participatory observation, interviews with teachers and principals, and collection of activity documents. Observations were made three times with different themes, namely traditional markets, hospitals, and post offices, to observe the gradual development of children's expressive language. The results showed that role-playing activities can improve various aspects of children's expressive language, such as the ability to express new vocabulary, compose sentences from simple to more complex, and the courage to ask questions and answer in relevant social contexts. Children can also make use of intonation and facial expressions according to the characters being played, as well as improvise in dialogue without completely relying on the teacher's instructions. Key elements that support the success of this activity include a fun learning environment, the availability of appropriate props, and teacher innovation in determining themes related to children's daily experiences. In conclusion, role-playing not only serves as a means of entertainment, but it has also proven to be successful as a contextual learning method that can encourage the development of expressive language in early childhood. This activity should be done regularly as part of learning in kindergarten so that children can become more confident, creative, and active in interacting.